PENINGKATAN PENGETAHUAN DAN TINDAKAN PETANI DALAM BUDIDAYA TANAMAN KOPI BERBASIS AGROFORESTRI - Ahmad Thoriq; Wahyu K Sugandi; Rizky Mulya Sampurno; Mochamad Arief Soleh (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
Coffee cultivation techniques play important roles in the productivity of coffee beans. This study aims to obtain information about knowledge and actions of farmers in coffee plantingin Genteng Village, Sukasari, Sumedang District. The research was conducted by direct survey method using a structured questionnaire to obtain primary data, while secondary data was obtained from government agencies. The data obtained were presented descriptively and analyzed using χ2 (chi-square). The results showed that most of the farmers (78%) had good knowledge oncoffee cultivation, while 18% of the farmers had moderate knowledge and 4% of the farmers had low knowledge. However, only 54% of the farmers took actions by applying recommended good coffee cultivation techniques. The level of knowledge of the farmers correlated with age and farming experience while farmer actions correlated with education level. The training contributed to increase in farmers' knowledge from 76% to 84.5%.